Pengaruh Sinetron Tukang Bubur Naik Haji Terhadap Kesadaran Masyarakat Dalam Mengeluarkan ZIS - Selina, Sera (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2014)
This study examines the influence of the religious television drama Tukang Bubur Naik Haji The Series on public awareness in paying zakat, infaq, and sadaqah (ZIS) among the residents of Cikeruh Village, Jatinangor District, Sumedang Regency. The research applies a quantitative correlational method using survey data collected from 94 respondents selected through proportionate stratified random sampling. The results show that the data are normally distributed, fulfilling the assumptions for linear regression analysis. The findings reveal that the message conveyed in the soap opera significantly affects public awareness of ZIS. Partial correlation analysis indicates a low correlation with zakat (r = 0.333), a strong correlation with infaq (r = 0.655), and a very strong correlation with sadaqah (r = 1.000). The coefficient of determination (Adjusted R² = 1.000) demonstrates that the message variable explains 100% of the variance in ZIS awareness. The study concludes that Tukang Bubur Naik Haji The Series serves as an effective medium for Islamic preaching (da’wah) through mass media, successfully combining entertainment and moral education. This research highlights the important role of religious media in shaping moral behavior and fostering social-religious awareness in contemporary Muslim society.